Cluster Analysis of the Eu Countries Which Turkey Has Textile Trade - Gündüz, Fatma Feyza; Gündüz, Selim; DÃ¶lekoğlu, Celile O. (International Journal of Economics and Financial Issues, 2018)
Textile and clothing sectors are industries which have formed by the separation of the textile industry, the oldest industry of the industrialization period, in itself. The branches of this industry have played an important part in the development of the developing countries accelerating the industrialization period during the period. The contribution of the textile and clothing industries which are labor-intensive industries to the economy in terms of labor force, foreign trade and new investments cannot be ignored. On the other hand, the industries in which competition capacity and branding speed are the highest are the textile and clothing industries. In this study, the export and import figures of the EU countries which make an important market in the textile industry with Turkey are analyzed by years. The foreign trade situation analysis in terms of protecting the competition capacity of Turkey is made and the differences and similarities between the member countries are tried to be determined. Hierarchical cluster analysis, which is one of the multivariate statistical methods, is applied to the import and export data of OECD between the years 2005 and 2016 and the countries within the EU market are extricated. Keywords: Textile Sector, Foreign Trade, Industrialization, Cluster Analysis, Situation Analysis JEL Classifications: M31, F10 https://doi.org/10.32479/ijefi.6886